Health Professional Perspectives on Rehabilitation for People With Dementia. (13th February 2019) - Cations, Monica; May, Natalie; Crotty, Maria; Low, Lee-Fay; Clemson, Lindy; Whitehead, Craig; McLoughlin, James; Swaffer, Kate; Laver, Kate E
Abstract: Background and Objectives: Multidisciplinary rehabilitation is not incorporated into the usual care pathway for dementia despite increasing demand from key advocates. Clinician views regarding the relevance of rehabilitation in dementia care are not well known. This qualitative study explored the perspectives of health professionals regarding barriers to provision of multidisciplinary rehabilitation programs for people with dementia. Research Design and Methods: Sixteen health professionals from a variety of settings and professional backgrounds were purposively sampled using maximum variation sampling. Semi-structured interviews were conducted to explore attitudes toward the care of people with dementia and beliefs about the feasibility and value of multidisciplinary rehabilitation in this population. Thematic analysis was used to identify themes. Results: Participating clinicians acknowledged problems with existing dementia care pathways in Australia but rarely conceptualized rehabilitation as relevant to this pathway. Analyses yielded two main and related themes: (i) difficulty defining worthwhile outcomes of a rehabilitation program for people with dementia and (ii) perceived barriers to participation in this population. Clinicians felt that achievable outcomes for people with dementia were not sufficiently worthwhile for investment. Discussion and Implications: Broader acceptance of multidisciplinary rehabilitation as relevant to dementia care will require a reframing of practice that both educates emerging health professionals regarding the outcomes that may be achievable for people with dementia and persuades staff to appreciate that the investment is worthwhile.